Ovarian hemangioma: A rare encounter - M. Singh; P. Subedi; B. Adhikari; A. Sherchan; A. Bajrachrya; S. Mohanty; H. P. Dhakal (Clinical Case Reports)
Key Clinical Message Ovarian hemangioma, though rare and asymptomatic, can mimic malignant ovarian tumors, thus it is necessary for comprehensive histopathological and immunohistochemical evaluation for accurate diagnosis and appropriate management.